Kokums to the Iskwêsisisak: COVID-19 and Urban Métis Girls and Young Women. Issue 3 (1st December 2020) - Jones, Carly; Monchalin, Renée; Bourgeois, Cheryllee; Smylie, Janet
Abstract: The national COVID-19 pandemic response presents a sharp contrast to the matrilineal social kinship and knowledge exchange systems that Métis women and girls rely on for safety, security, and wellbeing. In this article, we demonstrate that while Métis women and girls have been left out of the national pandemic response, they continue to carry intergenerational healing knowledges that have been passed down from the kokums (grandmas) to the iskwêsisisak (girls). We show how urban Métis girls and women are both managing and tackling COVID-19 through innovative and community-based initiatives like Well Living House and the Call Auntie Hotline .